Supercritical carbon dioxide extraction of trans-anethole from Foeniculum vulgare (fennel) seeds: Optimization of operating conditions through response surface methodology and genetic algorithm. (March 2019) - Mokhtari, Leila; Ghoreishi, S.M.
Graphical abstract: Highlights: Supercritical CO2 modified by ethanol was applied for trans-anethole extraction. The experiments and modeling were designed through response surface methodology. Response surface methodology and genetic algorithm were used to optimize conditions. The optimum recovery of trans-anethole was obtained 56.38 w/w% at optimum operating conditions by RSM model. GA optimum recovery of trans-anethole was obtained 55.50 w/w%. Abstract: The extraction of trans-anethole from fennel seeds is assessed by supercritical CO2 together with ethanol as the modifier. The experiments and modeling are designed through response surface methodology (RSM). The fennel extract is analyzed by gas chromatography-ﬂame ionization detector (GC-FID). RSM design and genetic algorithm (GA) are applied to optimize the SFE variables and trans-anethole recovery. The maximum trans-anethole recovery (56.38 w/w % and 55.50 w/w %) is obtained at optimal operating conditions at 21.3 and 21.55 MPa, 60.2 and 55.59 °C, 103 and 96.38 min and 1.74 and 1.49 ml/min of CO2 through RSM and GA, respectively. According to response surface analysis, R 2 and modiﬁed R 2 of the model are 96.64% and 93.71%, respectively. The accuracy of modeling optimal trans-anethole recovery is validated through triplicate experiments providing the average extraction recovery of 55.3 ± 1.5% and 54.5 ± 1.2% for RSM and GA, respectively.